Ethnic diversity makes me sick! An examination of ethnic diversity's effect on health outcomes - Sefa Awaworyi Churchill; Janet Exornam Ocloo; Diana Siawor-Robertson (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This study hypothesizes a relationship between ethnic diversity and health outcomes. We explore the effects of ethnic and linguistic heterogeneity (measured by indices of ethnic and linguistic fractionalization) on 30 health outcome variables in a cross-section of 87 countries. We explore outcomes related to four major categories of health: 1) immunization rates, 2) prevalence of diseases, 3) life expectancy and mortality rates, and 4) health related infrastructure and staff. Across all dimensions examined, evidence suggests that higher heterogeneity is bad for health. We explore several potential mechanisms which could explain the observed negative effects of ethnic and linguistic diversity on health.
Keywords: 330; health; Fractionalization; linguistic diversity; ethnic diversity